Trends in the Research of Children and Play - Akay, Buğra; Ceylan, Mehmet; Ayan, Sinan; Dündar, Hakan; Altun, Atilla (International Electronic Journal of Elementary Education, 2025)
The concept of play has long been recognized as a fundamental aspect of child development because it promotes learning and cognitive development, and is useful for social skills and motivation. So it has attracted the attention of researchers in many scientific fields such as maths, physical education, artificial intelligence and rehabilitation. Due to the importance of the relationship between children and play in various fields, it is essential to examine published works on this subject. This study aims to reveal the current status and trends of the research on children and play through the Web of Science database in 2023 by descriptive survey model. 165 articles were examined in depth, which examined studies in the field of "Children and Play". Content analysis technique and "Children and Play Research Publication Classification Form" developed by the researchers in a semi-structured manner were used for evaluating the data. The studies are generally under the themes of "Digital Games, Physical Games, Card Games, Traditional Games, Board Games and Mind Games". The studies are four different types: descriptive study, experimental (applied) study, evaluation study and other. The research includes thirteen different methods. Ten different data collection methods were used. It can be concluded that the studies done on "Children and Play" in 2023 are generally about digital games, and the relationship between play and health, behaviour, socialization and learning is the main theme.